In Remembrance of Dr. Samantha Rachel Gorse Roberts - Clayton B Bolton (Journal of Applied Sports Management, 2022)
Dr. Samantha Roberts, a professor at Texas A&M University-Commerce, was a significant member of the association’s leadership team. Dr. Roberts had a strong passion for student development and mentorship and was heavily involved with the undergraduate and graduate case study competitions. Dr. Clay Bolton provides a touching tribute to our dear colleague and friend.
Keywords: Dr. Roberts; tribute; ASMA